Translocation of the Alphanucleorhabdovirus X proteins from the cytoplasm into the nucleus through interaction with nucleocapsid protein is essential for viral pathogenesis - Shuo Wang; Shuang Ni; Huanhuan Lou; Yan Liang; Zhenghe Li (Phytopathology Research)
Abstract The diverse rhabdoviruses infecting plants and animals have conserved genome organizations, and the functions of viral structural proteins have been extensively studied. However, increasing number of rhabdoviruses have been found to encode various accessory proteins, whose specific roles during viral infection remain poorly understood. In this study, we investigated the function of the X proteins encoded by several members of the genus Alphanucleorhabdovirus. Using the recently established eggplant mottled dwarf virus (EMDV) reverse genetics system, we found that recombinant EMDV lacking the X gene was able to systemically infect Nicotiana benthamiana plants, albeit with reduced efficiency. However, this deletion mutant was largely restricted to the veinal tissues and caused asymptomatic infections. The EMDV X protein, which localized to the cytoplasm when expressed alone, was translocated to the nucleus via a specific interaction with the nucleocapsid (N) protein. Through analyzing the interactions of the X deletion mutants and the infection phenotypes of the derived EMDV deletion mutants, we demonstrated that the carboxyl-terminal region of the X protein (amino acids 71–83) is crucial for its interaction with the N protein and for viral pathogenesis. Moreover, the X proteins encoded by related alphanucleorhabdoviruses could fully or partially complement the functions of EMDV X in viral infection. These findings provide new insights into the roles of accessory proteins in plant rhabdovirus infection.